2000
DOI: 10.1126/science.288.5463.133
|View full text |Cite
|
Sign up to set email alerts
|

Sink or Swim: Strategies for Cost-Efficient Diving by Marine Mammals

Abstract: Locomotor activity by diving marine mammals is accomplished while breath-holding and often exceeds predicted aerobic capacities. Video sequences of freely diving seals and whales wearing submersible cameras reveal a behavioral strategy that improves energetic efficiency in these animals. Prolonged gliding (greater than 78% descent duration) occurred during dives exceeding 80 meters in depth. Gliding was attributed to buoyancy changes with lung compression at depth. By modifying locomotor patterns to take advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
348
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(368 citation statements)
references
References 27 publications
15
348
0
2
Order By: Relevance
“…Previous studies suggest that marine mammals may reduce swimming costs by employing prolonged gliding aided by negative buoyancy during the descent phase of dives [15,16,22]. This was confirmed by experimental modification of buoyancy in seals [17,23].…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies suggest that marine mammals may reduce swimming costs by employing prolonged gliding aided by negative buoyancy during the descent phase of dives [15,16,22]. This was confirmed by experimental modification of buoyancy in seals [17,23].…”
Section: Introductionsupporting
confidence: 66%
“…During descent, the proportion of time spent in prolonged gliding remained high when seals were negatively buoyant (range ¼ 0.4-0.9; figure 2). This indicates that seals largely relied on negative buoyancy as the thrust force for gliding, which kept their stroking effort low [15,17]. In addition, descent pitch angles were steeper when seals were more buoyant (electronic supplementary material, figure S5), which might allow seals to descend with less stroking activity because a steeper pitch angle would bring the vector of forward motion closer to that of the force of gravity [16].…”
Section: Discussion (A) Buoyancy Determines Locomotor Costs Of Swimmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect measurements have suggested that the depth where gas exchange ceases is between 30m (Falke et al, 1985) and 70m (Ridgway and Howard, 1979), but direct measurements of animals diving with a lung volume of only 18% of TLC indicate that complete shunt may not occur until a depth of 170m (Kooyman and Sinnett, 1982). Studies of maximal depth of neutral buoyancy, which has to be at a depth less than atelectasis (Biuw et al, 2003;Skrovan et al, 1999;Williams et al, 2000), agree with the pulmonary shunt data published by Kooyman and Sinnett showing that the collapse occurs at depths below 100m (Kooyman and Sinnett, 1982). Our results using the hyperbaric chamber suggest these last estimates have worth.…”
Section: Discussionmentioning
confidence: 99%